2020
DOI: 10.1136/bmjopen-2020-036862
|View full text |Cite
|
Sign up to set email alerts
|

Changes over a decade in psychotropic prescribing for people with intellectual disabilities: prospective cohort study

Abstract: ObjectivesTo investigate psychotropic prescribing in the intellectual disabilities population over 10 years, and associated mental ill health diagnoses.DesignComparison of cross-sectional data in 2002–2004 (T1) and 2014 (T2). Longitudinal cohort study with detailed health assessments at T1 and record linkage to T2 prescribing data.SettingGeneral community.Participants1190 adults with intellectual disabilities in T1 compared with 3906 adults with intellectual disabilities in T2. 545/1190 adults with intellectua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…2017; Henderson et al . 2020) and such cumulative effects may therefore negatively impact the health and wellbeing of this population. (2) Our results are similar to both Joos et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2017; Henderson et al . 2020) and such cumulative effects may therefore negatively impact the health and wellbeing of this population. (2) Our results are similar to both Joos et al .…”
Section: Discussionmentioning
confidence: 99%
“…2016; Henderson et al . 2020) for all people with ID along with appropriate training for staff to recognise DDIs and mitigate for diagnostic overshadowing (Mason and Scior 2004). (5) Given that our findings highlight that there were 320 instances where people should be provided with further information regarding potential adverse effects, there is also a critical need to ensure that people with ID are provided with an appropriate and understandable level of medication‐related information (O'Dwyer et al .…”
Section: Discussionmentioning
confidence: 99%
“…3 A study from Scotland reported that over the decade from 2004 to 2014, there was an increase in the prescription of antidepressants from 11.2 to 19.1%. 5 The increase was greatest for women and people with mild intellectual disabilities. 5…”
Section: Antidepressant Prescribing In People With Intellectual Disab...mentioning
confidence: 99%
“…28 People with intellectual disabilities are particularly vulnerable, with commonplace psychotropic polypharmacy as well as overall anticholinergic polypharmacy. Many people with intellectual disabilities are on antipsychotic medication over years and sometimes decades, 14,29 despite associated health risks, including anticholinergic effects. However, following NHS England's "Stopping over-medication of people with a learning disability, autism or both (STOMP)" initiative, 11 there is some evidence of successful antipsychotic deprescribing, 30 but these prescriptions may be being replaced with other psychotropics, namely antidepressants, 31 which could contribute to anticholinergic burden similarly.…”
Section: Discussionmentioning
confidence: 99%